2008
DOI: 10.1139/z08-037
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors affecting growth of eastern sand darter (Ammocrypta pellucida)

Abstract: Environmental factors affecting growth of the threatened eastern sand darter ( Ammocrypta pellucida (Putnam, 1863)) were examined using specimens sampled from the northern edge of its range to determine the species’ critical habitat. Length-at-age increments were determined from scale samples as surrogates for growth rates based on back-calculated lengths using the Fraser–Lee method. During the first year of life, 82% of total length is attained, suggesting considerable energetic partitioning towards reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Substrate composition is thought to be a factor affecting Eastern Sand Darter habitat utilization because of their characteristic burrowing (Drake et al 2008), and our aquarium study supports the observations of others (see Grandmaison et al 2004 * ) that sand darters tend to burrow. Therefore, changes in substrate composition could impact the fish's ability to use certain areas.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Substrate composition is thought to be a factor affecting Eastern Sand Darter habitat utilization because of their characteristic burrowing (Drake et al 2008), and our aquarium study supports the observations of others (see Grandmaison et al 2004 * ) that sand darters tend to burrow. Therefore, changes in substrate composition could impact the fish's ability to use certain areas.…”
Section: Discussionsupporting
confidence: 91%
“…The Eastern Sand Darter may be unable to burrow easily into 244 THE CANADIAN FIELD-NATURALIST Vol. 122 Drake et al (2008) showed that age-0 Eastern Sand Darters grew better in areas with more sand than in areas with more silt, and argued that sand-dominated substrates would be energetically beneficial because of higher oxygen levels and greater prey availability. Some regulations for protecting river water quality, including prevention of excess sediment input, have probably decreased silt loads and improved habitat for the Eastern Sand Darter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations